Penetapan Anak Angkat sebagai Ahli Waris di Pengadilan Agama Lubuk Pakam Nomor 1619/Pdt.G/2019/PA - Hermawan, Randi; Harahap, M. Yadi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Adopting a child is a legal act, therefore this act has legal consequences. One of the legal consequences of the adoption of a child is regarding the adopted child's status as the heir of his or her adoptive parents. This status often causes problems within the family. The issues that often arise in cases of lawsuits are usually regarding whether or not the adoption of the child is legal, as well as the position of the adopted child as the heir of his or her adoptive parents. According to civil law in Staatsblad 1917 No. 129, the adoption of a child results in the child's status as if they were born from the marriage of adoptive parents. So the status of an adopted child is the same as a legitimate child and in inheritance law he is also called an heir. In the event that the inheritance of an adopted child in the Compilation of Islamic Law is not giving up the lineage (relatives) of his biological parents, then the adopted child does not inherit from his adoptive parents and vice versa, but the adopted child gets a mandatory will, namely a will whose implementation is not influenced or does not depend on the will or the will of the deceased. The amount cannot be more than 1/3 of the inheritance of the adoptive parents in accordance with Article 209 paragraph (2) of the Compilation of Islamic Law. And in the decision of the Lubuk Pakam religious court, how does the judge decide whether an adopted child will be the heir? (KHI).